PENGARUH PROFITABILITAS, LEVERAGE, DAN AKTIVITAS TERHADAP PERTUMBUHAN LABA PERUSAHAAN MANUFAKTUR - Sutio, Jovan; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to analyze the effect of profitability, leverage, and activity on profit growth of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The method used for data analysis in this study is multiple linear regression analysis using Eviews version 12. The sample selection technique used is puposive sampling and obtained 55 manufacturing companies in the 2017-2019 period so that the total sample in this study is 165 samples. The results found that simultaneously profitability, leverage, and activity influence profit growth. Partial testing shows that both profitability and activity have a significant and positive effect while leverage has a significant and negative effect on profit growth.